The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1017/s0031182000074266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone onHeterakis spumosainfections in mice

Abstract: This study describes the effects of testosterone (Te) on the intestinal nematode Heterakis spumosa in mice. The course of Heterakis infections is apparently under Te-control. At high circulating Te-levels as occurring in intact males, Te-treated females, and Te-treated castrated males, the period of release of Heterakis eggs in mouse faeces is greatly extended and the number of eggs released per unit time is markedly elevated in comparison to low Te-levels, as found in untreated females and castrated male mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 29 publications
(25 reference statements)
2
13
0
Order By: Relevance
“…Males have higher blood levels of testosterone, a hormone presumed to have an immunosuppressive effect (Owens and Wilson 1999). Testosterone supplementation can reduce spleen size in mice (Harder et al 1992). We consider that this factor may explain the sexdependent nature of the relationships between nematode abundance and body condition and between spleen size and colour brightness…”
Section: Fig 1 Relationship Between Body Mass (Standardized By Regrmentioning
confidence: 96%
“…Males have higher blood levels of testosterone, a hormone presumed to have an immunosuppressive effect (Owens and Wilson 1999). Testosterone supplementation can reduce spleen size in mice (Harder et al 1992). We consider that this factor may explain the sexdependent nature of the relationships between nematode abundance and body condition and between spleen size and colour brightness…”
Section: Fig 1 Relationship Between Body Mass (Standardized By Regrmentioning
confidence: 96%
“…According to Harder et al 15 , rodent males would be more susceptible to parasitic infections because of the deleterious effect of testosterone, which impairs the hosts' immunological response. However, Eloi-Santos et al 10 found that Schistosoma mansoni cercariae were more successful in developing into adult worms in experimentally infected female mice, when compared to male mice exposed to the same number of cercariae.…”
Section: Tablementioning
confidence: 99%
“…Testosterone treatment in mice aects the development and growth of another nematode, Heterakis spumosa, by prolonging the period of infection (Harder et al 1992). It has also been reported that S. ratti L3 migration is aected by the temperature and sodium concentration to which the parasites are exposed (Tobata and Shimada 1996;personal communication).…”
Section: Discussionmentioning
confidence: 98%